2011
DOI: 10.3390/molecules16086684
|View full text |Cite
|
Sign up to set email alerts
|

3D-QSAR Study of Combretastatin A-4 Analogs Based on Molecular Docking

Abstract: Combretastatin A-4 (CA-4), its analogues and their excellent antitumoral and antivascular activities, have attracted considerable interest of medicinal chemists. In this article, a docking simulation was used to identify molecules having the same binding mode as the lead compound, and 3D-QSAR models had been built by using CoMFA based on docking. As a result, these studies indicated that the QSAR models were statistically significant with high predictabilities (CoMFA model, q2 = 0.786, r2 = 0.988). Our models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…The optimized geometries and natural charges calculated for non-hydrogen atoms are almost identical with the exception of the nitrogens on the azo bridge. Because the aromatic groups and their methoxy substituents are the major contributors to tubulin binding in CA4, 33 based on structure alone, we would expect that Azo-CA4 would be a potent tubulin inhibitor and act similarly to CA4.…”
Section: Resultsmentioning
confidence: 99%
“…The optimized geometries and natural charges calculated for non-hydrogen atoms are almost identical with the exception of the nitrogens on the azo bridge. Because the aromatic groups and their methoxy substituents are the major contributors to tubulin binding in CA4, 33 based on structure alone, we would expect that Azo-CA4 would be a potent tubulin inhibitor and act similarly to CA4.…”
Section: Resultsmentioning
confidence: 99%
“…CA-4 and its water-soluble prodrugs such as CA-4P (fosbretabulin and zybrestat) [4] and AVE8062 (ombrabulin) [5] have entered clinical trials for the treatment of anaplastic thyroid cancer and other solid tumors in both USA and Europe [6]. Due to its small molecular weight and simple structure, an impressive number of synthetic research was carried out over the past decades [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…6 Several structure-activity relationship studies of CA-4 has revealed that the cis configuration of the double bond, the 3,4,5-trimethoxy groups on the A-ring, and the meta-hydroxy and para-methoxy groups on the B-ring are fundamental for its main biological activity. 7 Thereby, CA-4 has inspired the synthesis and biological evaluation of different cytotoxic analogues containing these privileged pharmacophores: the disodium phosphate prodrug CA-4P 2, 8 colchicine 3, 9 podophyllotoxin 4, 10 eugenol 5 11 and some oxindole derivatives 6-7 12 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%